AB0568 Biologics in Takayasu Arteritis: Preliminary Data from the French Registry. (10th June 2014) - Mekinian, A.; Mirault, T.; Lambert, M.; Sibilia, J.; Hie, M.; Comarmond, C.; Messas, E.; Berthier, S.; Neel, A.; Hamidou, M.; Cohen, P.; Marie, I.; et al.
Abstract : Objectives: The aim of this registry is to determine: (1) the real-life use of various biologics in Takayasu arteritis in France; (2) to compare the efficacy of different biologics among them; (3) to evaluate the tolerance; (4) to describe the long term outcome. Methods: All French practionners from the departments of internal medicine, of vascular medicine and rheumatology will be regularly contacted to declare the patients with TA under biologics. The clinical, biological and radiological data are collected in standardized fill at the baseline, at 6, 12, 24 months and the last visit. All radiological exams will be reviewed by two radiologists blinded to the clinical and biological data. The response to the biologics will be assessed using NIH score, and the outcome will be compared at the least visit to the baseline. The disease activity was determined using the NIH score. Results: Forty two patients with TA (age 42±15 years, 36 women) were included. At the initiation of biologics, 91% of patients were treated with steroids (prednisone mean amount 27±20 mg/day). Another immunosuppressive agent was associated in 88%: methotrexate (56%), azathioprine (34%) and mycophenolate mofetil (3%). Steroid dependence was noted in 41% of patients. At the time of the biologics initiation the clinical symptoms were upper limb claudication (35%), carotidynia (32%), arterial hypertension (21%), headaches (24%), fever (9%), arthromyalgias (35%), and arterial vascular stroke (12%). Associated disease was noted in 24% of cases: spondyloarthritis (15%), Crohn disease (6%) and sarcoidosis (1%). The various biologics were used in 48 cases for 42 patients. Among them, the biologics was infliximab (52%), etanercept (14%), adalimumab (10%), tocilizumab (31%), anakinra (2%) and rituximab (5%). The biologics duration was 1.8±1.1 year, with the mean follow-up of 3±1.5 years. Two infusion related reactions were noted, one myocardial infarction and 4 severe infections. One patient under tocilizumab experienced adverse effect which was severe neutropenia (<500/mm 3 ), but without any infection or antibiotics needs in relation with tocilizumab. The neutropenia needed the decrease of tocilizumab from 8 mg/kg to mg/kg and was then well-tolerated. No death related to biologics treatment was noted. Conclusions: This is the french registry of TA treated by biologics which aim to describe the real life use of biologics in TA, to compare the different agents and to determine the factors predictives of the treatment response. The registry is ongoing and the efficacy and the tolerance of different biologics will be compared. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5308